Duration of Reproductive Life Span, Age at Menarche, and Age at Menopause Are Associated With Risk of Cardiovascular Disease in Women - Sylvia H. Ley; Yanping Li; Deirdre K. Tobias; JoAnn E. Manson; Bernard Rosner; Frank B. Hu; Kathryn M. Rexrode (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundAlthough the timing of menarche and menopause may be associated with cardiovascular disease (CVD), the entire reproductive life span has not been considered comprehensively as risk for CVD. We investigate the associations of reproductive life span duration and ages at menarche and menopause, induced by natural means or surgical bilateral oophorectomy, with incident CVD in women. Methods and ResultsProspective cohort study of 73 814 Nurses' Health Study following participants without CVD, defined as incident coronary heart disease or stroke, from 1980 through 2012. Duration of reproductive life span was generated by subtracting age at menarche from age at menopause. A shorter reproductive life span was associated with a higher risk of incident CVD after multivariable adjustment (relative risk, 1.32 [95% confidence interval, 1.16–1.49] comparing duration <30 with ≥42 years; P trend<0.0001). Early age at menopause was associated with higher multivariable‐adjusted CVD risk (1.32 [1.16–1.51] comparing age <40 with 50 to <55 years; P trend<0.0001), with excess risk for both natural and surgical menopause. Compared with women with menarche at 13 years, the multivariable‐adjusted CVD risk for early menarche at ≤10 years was 1.22 (1.09–1.36). The association between reproductive life span and CVD remained significant in sensitivity analyses excluding women who experienced extreme early age at menarche or who used hormone therapy. ConclusionsA shorter duration of reproductive life span is associated with a higher risk of CVD, which is likely driven by the timing of menopause induced either naturally or surgically. Extremely early age at menarche is also associated with a higher risk of CVD.